Optimal consumption and taxation of housing: A life cycle approach - Ulrich van Suntum (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2008)
A simple OLG-model is developed, where housing is the only consumption good and saving is either in terms of financial assets or in terms of owner-occupied or rented dwellings. It is shown that, while without taxes optimal consumption plans and maximum utility are the same for both the tenant and the owner-occupier, conventional income taxes cause a bias in favour of the latter. It is argued that the consumption good approach is always advantageous for the owner-occupier in comparison with the investment approach, even with high interest rates and a high share of borrowing. However, even the investment approach does not entirely remove the taxation bias on the expense of the tenant, unless the latter is allowed to deduct total interest payments from his income. An alternative could be cash-flow taxation. It is also shown that the conventional investment approach is equivalent to - and therefore could be replaced by - a much simpler version, where instead of imputed rent imputed interest on net capital is taxed.
Keywords: 330